Analysis of Factors Affecting Defense Expenditures: An XAI-Based Model - Kisman, Zulfukar Aytac; Uzun, Selman; Guler, Mustafa Ali; Bakal, Ceren; Kirac, Ziya Kivanc; Yildirim, Gungor; Alatas, Bilal (Mdpi, 2026)
This paper investigates how economic capacity, budget priorities, and governance conditions jointly shape defense spending in a transparent and auditable empirical framework. Using annual cross-country data for 2002-2023 compiled from widely used international sources, we evaluate the relative importance of economic indicators, fiscal allocation patterns, and institutional factors in explaining defense expenditure outcomes. We use Explainable Artificial Intelligence (XAI) to quantify the relative contribution of these factors in a transparent and interpretable manner. The results show that economic capacity and the way governments prioritize defense within overall public finances are the strongest and most consistent drivers of defense spending differences across countries. Governance conditions act as an institutional filter that can constrain or intensify these effects: more democratic and accountable environments tend to limit increases in defense spending, whereas lower political stability is associated with upward spending pressure. These findings are important because they clarify that defense expenditure is not determined by a single factor, but by a layered interaction between resources, priorities, and institutions. The study contributes a replicable and policy-relevant approach for interpreting defense spending dynamics and for supporting accountable decision-making in defense budgeting.
Keywords: defense expenditures; governance indicators; macroeconomics; explainable artificial intelligence